Семейный альбом - Стил Даниэла (Звезда любви, 1995)
Экземпляры: Атабаевская с/б (20240604) / Инвентарный номер: 48275 / Цена: / Сис.шифр: 84(7Сое)-44 / Авт.знак: С 80 / ГРНТИ: 17.82.31 / ББК: 84(7Сое)-44